Human cytomegalovirus-induced immediate early antigens: analysis in sodium dodecyl sulfate-polyacrylamide gel electrophoresis after immunoprecipitation. - Michelson, S (1979)
Immediate early antigen (IEA) induced in human lung fibroblasts by human cytomegalovirus was characterized by sodium dodecyl sulfate-polyacrylamide gel electrophoresis analysis after immunoprecipitation with IEA-positive human sera. Two polypeptides of 76,000 daltons (76K) and 82K were detectable within 90 min after infection. Polypeptides of similar molecular weight were also found in immunoprecipitates of human cytomegalovirus-infected cells nonpermissive for virus replication. IEA is located within the nucleus, although some of the 76K material appears to be located on the outer nuclear membrane. Raising salt concentrations in the extraction buffer increased antigen extraction. The contribution of these IEA polypeptides to IEA nuclear fluorescent staining is discussed.